ANALISIS PENJALARAN KEKERINGAN METEOROLOGI MENUJU KEKERINGAN HIDROLOGI PADA DAS LARONA - Ika Purnamasari; Hidayat Pawitan; Findy Renggono (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Hydrological drought is water deficit from normal conditions on the hydrological system. Hydrological drought occurs through a complex process preceded by a rainfall deficit. The series of processes that show a change of drought signals through the hydrological cycle is expressed as drought propagation. This study aims to identify the characteristics of hydrological and meteorological drought and to identify meteorological drought propagation to hydrological drought through Larona Watershade. Standardized Precipitation Index (SPI) is used as indicator to identify meteorological drought while hydrological drought is characterised by Standardised Streamflow Index (SSI) with 1, 3, 6 and 12 months accumulation periods. Propagation meteorological drought to hydrological drought was analyzed using Pearson correlation. The results showed that duration and severity escalate by the increase in the accumulation period SPI and SSI. While the number of drought events is inversely proportional to the accumulation period SPI and SSI. Althought the number of hydrological drought events was fewer, but they occurred over longer duration and much severe than the meterological one. Severe hydrological drought (SSI 1 = -14.8) in 1997-1998 has declined water storage of Lake Towuti by 90% leading to reduction in Larona hydropower production. Furthermore, our findings provide promising approach to detect hydrological drought that may occur in the near future.